Isolasi fragmen gen LIPASE dari kapang Absidia corymbifera, Rhizopus oryzae dan Rhizopus oligosporus Isolation of LIPASE gene fragment from Absidia corymbifera, Rhizopus oryzae and Rhizopus oligosporus fungi - Riza A. PUTRANTO; Asmini BUDIANI (E-Journal Menara Perkebunan, 2009)
AbstractDiversification of oil palm products, suchas healthy oil, needs lipase sustainability as abiocatalist. Many attempts have beendeveloped to produce lipase, includingintensive exploration and screening of severalspecies of molds. Genetic engineering for overexpression of LIPASE gene in the selectedmold is considered to be the potentialapproach for efficient production of thisenzyme. This research was aimed to isolate theLIPASE gene fragment of Indonesianindigenous fungi, namely Absidia corymbifera,Rhizopus oryzae and R. oligosporus by meansof RT-PCR (Reverse Transcriptase PolymeraseChain Reaction) technique using heterologousprimers. The result showed that a cDNAfragment of 462 bp has been amplified andisolated from the three fungi with differentconcentration. The highest quantity was foundfrom A. corymbifera. The RT-PCR productsisolated from A. corymbifera was cloned,sequenced and analyzed for its homology to thesequence of LIPASE gene from other species.BLAST analysis showed that the DNA sequenceof the cloned RT-PCR product derived fromA. corymbifera was highly homologous withLIPASE gene from Rhizopus niveus.AbstraksDiversifikasi produk kelapa sawit, sepertiminyak sehat (healthy oil) memerlukanketersediaan lipase sebagai biokatalis. Berbagaiupaya untuk produksi lipase telah dikembang-kan, termasuk eksplorasi dan skrining terhadapbeberapa spesies kapang secara intensif.Rekayasa genetika untuk mengoverekspresi-kan gen LIPASE pada kapang hasil skriningtersebut dipandang merupakan satu pendekatanpotensial untuk produksi enzim ini secaraefisien. Penelitian ini bertujuan untukmengisolasi fragmen gen LIPASE dari tigakapang indigenous Indonesia, yaituA. corymbifera, R. oryzae dan R. oligosporus,menggunakan teknik RT-PCR (ReverseTranscriptase Polymerase Chain Reaction).Hasil penelitian menunjukkan bahwa fragmencDNA sepanjang 462 bp dari ketiga kapangtelah diisolasi, masing-masing dengankuantitas yang berbeda. Hasil tertinggidiperoleh dari kapang A. corymbifera. ProdukRT-PCR dari A. corymbifera diklon, disekuenkemudian dianalisis homologinya dengansekuen gen LIPASE dari spesies lain. AnalisisBLAST menunjukkan bahwa sekuen DNA dariproduk RT-PCR terklon yang berasal dariA. corymbifera memiliki homologi tinggidengan gen LIPASE dari Rhizopus niveus.